Solid electrolyte membrane, all-solid-state battery, preparation method of all-solid-state battery and vehicle

By adopting a composite solid electrolyte membrane structure in an all-solid state battery, combining halide and polymer electrolyte membrane, and introducing binders and inorganic fillers, the chemical compatibility problem of halide and sulfide electrolyte membrane in the contact area is solved, and the battery's magnification and cycling performance are significantly improved.

CN119560623APending Publication Date: 2025-03-04ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510063972.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The chemical compatibility of existing halide and sulfide solid electrolyte membranes in the contact area is poor, resulting in unstable interfaces and affecting the rate performance and cycling performance of all-solid state batteries.

Method used

The composite solid electrolyte membrane structure is adopted, including a combination of a halide solid electrolyte membrane and a polymer solid electrolyte membrane. Through the introduction of binders and inorganic fillers, the mechanical properties and ionic conductivity of the membrane are improved and compatibility with the lithium metal negative electrode is enhanced.

Benefits of technology

It improves the rate performance and cycling performance of all solid-state batteries, enhances the energy density and mechanical stability of the batteries, and improves the overall performance of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560623A_ABST
    Figure CN119560623A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to a solid-state electrolyte membrane, an all-solid-state battery, a preparation method of the all-solid-state battery and a vehicle. The solid electrolyte membrane comprises a halide solid electrolyte membrane and a polymer solid electrolyte membrane compounded on one side of the halide solid electrolyte membrane, the halide solid electrolyte membrane comprises a halide solid electrolyte and a binder, and the polymer solid electrolyte membrane comprises a polymer solid electrolyte, a lithium salt and an inorganic filler. According to the solid-state electrolyte membrane provided by the invention, the halide solid-state electrolyte membrane and the polymer solid-state electrolyte membrane are compounded, so that the interface compatibility between the halide solid-state electrolyte membrane and the polymer solid-state electrolyte membrane can be improved while the compatibility with a lithium metal negative electrode is realized; and the rate capability and the cycle performance of the all-solid-state battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a solid-state electrolyte membrane, an all-solid-state battery, a preparation method thereof, and a vehicle. Background Art

[0002] All-solid-state batteries have become a promising next-generation energy storage technology due to their high energy density and high safety. The development of solid electrolytes with high room temperature ionic conductivity, excellent chemical / electrochemical stability, and good positive / negative electrode compatibility is the key to realizing the practical application of all-solid-state batteries. Compared with other electrolytes, halide solid electrolytes have advantages such as excellent electrochemical window, high positive electrode stability and acceptable room temperature ionic conductivity, and have thus attracted widespread attention. Lithium metal has broad development prospects in solid-state batteries. However, in practical applications, due to the low electronegativity of lithium, most electrolytes with transition metal components are reduced when in contact with lithium metal, forming an unstable interface. Halide solid electrolytes contain various high-valent metal elements and will also face such interface problems. In addition, in order to improve the energy density of solid-state batteries, the solid electrolyte layer needs to have a thin thickness and high ionic conductivity. Therefore, halide solid electrolytes not only need to reduce their own thickness, but also need to improve the interfacial compatibility with lithium negative electrode materials.

[0003] CN115458801A prepares halide solid electrolyte membrane and sulfide solid electrolyte membrane respectively by wet process, and after stacking halide solid electrolyte membrane and sulfide solid electrolyte membrane, composite electrolyte membrane for all-solid-state lithium battery is prepared. The composite electrolyte membrane not only has the advantages of high mechanical strength, high ionic conductivity, ultra-thinness and high toughness, but also can be compatible with high voltage positive electrode and lithium negative electrode at the same time, and can be used in lithium metal battery to reduce its safety risk. However, the latest research found that indium sulfide-rich components were detected in the contact area between halide and sulfide, which can be inferred that the chemical compatibility of the two electrolytes is poor.

[0004] It can be seen that the combination of halide membrane and sulfide membrane seems not ideal. Therefore, the present invention provides a new solid electrolyte membrane to solve the above problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a solid electrolyte membrane, an all-solid-state battery and a preparation method and a vehicle thereof.

[0006] In a first aspect, the present invention provides a solid electrolyte membrane, which includes a halide solid electrolyte membrane and a polymer solid electrolyte membrane composited on one side thereof, wherein the halide solid electrolyte membrane includes a halide solid electrolyte and a binder, and the polymer solid electrolyte membrane includes a polymer solid electrolyte, a lithium salt and an inorganic filler.

[0007] As a preferred technical solution of the present invention, the halide solid electrolyte includes Li a M1X6、Li b M2X4 and Li 3-c M3 1-c M4 c Any one or more of X6;

[0008] Among them, 2≤a≤3, 0 <b≤2,0<c<1;

[0009] M1, M3 and M4 are each independently selected from any one of Sc, Y, La-Lu, In, Er, Yb, Zr or Hf; M2 is selected from any one or more of Co, Zn, Al, Cr, Mg or Ni, wherein La-Lu refers to lanthanide elements;

[0010] X is selected from any one or more of F, Cl, Br or I.

[0011] As a preferred technical solution of the present invention, M3 is In, M4 is selected from Zr or Sc, and X is selected from F or Cl;

[0012] Or, M3 is Y or Er, M4 is Zr, and X is Cl;

[0013] Or, M3 is Yb, M4 is selected from Zr or Hf, and X is Cl.

[0014] As a preferred technical solution of the present invention, the binder includes PTFE.

[0015] As a preferred technical solution of the present invention, the polymer solid electrolyte includes any one or more of PEO, PMMA, PAN, PS and PVDF.

[0016] As a preferred technical solution of the present invention, the lithium salt includes any one or more of LiTFSI, LiDFOB, LiPF6, LiBF4, LiBOB, LiFSI and LiPO2F2.

[0017] As a preferred technical solution of the present invention, the inorganic filler includes any one or more of LLZTO, LATP, LLZO, LLTP, LiPON and LZG.

[0018] As a preferred technical solution of the present invention, based on the total mass of the halide solid electrolyte membrane being 100%, the content of the halide solid electrolyte is 95-98%, and the content of the binder is 2-5%.

[0019] As a preferred technical solution of the present invention, based on the total mass of the polymer solid electrolyte membrane being 100%, the content of the polymer solid electrolyte is 45-48%, the content of the inorganic filler is 12-15%, and the content of the lithium salt is 40%.

[0020] As a preferred technical solution of the present invention, the thickness of the halide solid electrolyte membrane is 80-100 μm.

[0021] As a preferred technical solution of the present invention, the thickness of the polymer solid electrolyte membrane is 80-120 μm.

[0022] Accordingly, the present invention provides a method for preparing the solid electrolyte membrane, the method comprising:

[0023] (1) mixing a halide solid electrolyte and a binder and rolling them to obtain a halide solid electrolyte membrane;

[0024] (2) mixing a polymer solid electrolyte, a lithium salt, an inorganic filler and a solvent to obtain a polymer solid electrolyte slurry, and coating the polymer solid electrolyte slurry on the surface of the halide solid electrolyte membrane to obtain the solid electrolyte membrane;

[0025] Alternatively, the polymer solid electrolyte slurry is cast to obtain a polymer solid electrolyte membrane, which is then composited with the halide solid electrolyte membrane to obtain the solid electrolyte membrane.

[0026] As a preferred technical solution of the present invention, the solvent in step (2) includes N-methylpyrrolidone (NMP).

[0027] In a second aspect, the present invention provides an all-solid-state battery, comprising the solid electrolyte membrane described in the first aspect.

[0028] In a third aspect, the present invention provides a method for preparing an all-solid-state battery as described in the second aspect, the preparation method comprising:

[0029] (1) rolling and laminating the halide solid electrolyte membrane and the positive electrode plate to obtain an integrated positive electrode, and coating the polymer solid electrolyte slurry on the surface of the negative electrode plate to obtain an integrated negative electrode;

[0030] (2) rolling the integrated positive electrode and the integrated negative electrode to obtain the all-solid-state battery;

[0031] Or, the preparation method comprises:

[0032] (1) coating a polymer solid electrolyte slurry on the surface of the halide solid electrolyte membrane to obtain a solid electrolyte membrane;

[0033] Or, a polymer solid electrolyte membrane is obtained by casting a polymer solid electrolyte slurry and then compounded with the halide solid electrolyte membrane to obtain a solid electrolyte membrane;

[0034] (2) Compounding the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet to obtain the all-solid-state battery;

[0035] The preparation method of the halide solid electrolyte membrane comprises: mixing the halide solid electrolyte and the binder and rolling them to obtain the halide solid electrolyte membrane;

[0036] The preparation method of the polymer solid electrolyte slurry comprises: mixing a polymer solid electrolyte, a lithium salt, an inorganic filler and a solvent to obtain the polymer solid electrolyte slurry.

[0037] In a fourth aspect, the present invention provides a vehicle, comprising the all-solid-state battery described in the second aspect.

[0038] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:

[0039] The solid electrolyte membrane provided by the present invention combines a halide solid electrolyte membrane and a polymer solid electrolyte membrane, thereby achieving compatibility with a lithium metal negative electrode while improving the interface compatibility between the halide solid electrolyte membrane and the polymer solid electrolyte membrane, thereby effectively improving the rate performance and cycle performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0042] Figure 1 This is a flow chart for preparing the battery cell described in Example 6 of the present invention. DETAILED DESCRIPTION

[0043] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0046] The halide solid electrolyte contains various high-valent metal elements, which are reduced when in contact with lithium metal, forming an unstable interface. In the prior art, the halide film is compounded with the sulfide film in order to improve its interface problem, but the latest research has found that components rich in indium sulfide are detected in the contact area between the halide and the sulfide, which can be inferred that the chemical compatibility of the two electrolytes is poor. In addition, in order to improve the energy density of the solid-state battery, the solid electrolyte layer also needs to have a thinner thickness and high ionic conductivity. Therefore, the embodiments of the present invention provide a new solid electrolyte membrane, an all-solid-state battery, a method for preparing the same, and a vehicle.

[0047] First, an embodiment of the present invention provides a solid electrolyte membrane, which includes a halide solid electrolyte membrane and a polymer solid electrolyte membrane composited on one side thereof, the halide solid electrolyte membrane includes a halide solid electrolyte and a binder, and the polymer solid electrolyte membrane includes a polymer solid electrolyte, a lithium salt and an inorganic filler.

[0048] The solid electrolyte membrane provided in the embodiment of the present invention is a composite of a halide solid electrolyte membrane and a polymer solid electrolyte membrane, which can achieve compatibility with the lithium metal negative electrode while improving the interface compatibility between the halide solid electrolyte membrane and the polymer solid electrolyte membrane, thereby effectively improving the rate performance and cycle performance of the all-solid-state battery. Specifically:

[0049] The solid electrolyte membrane provided in the embodiment of the present invention includes a halide solid electrolyte membrane and a polymer solid electrolyte membrane composited on one side thereof. On the one hand, the polymer solid electrolyte in the polymer solid electrolyte membrane gives the electrolyte membrane good mechanical properties, and the introduction of lithium salt can provide better ion conductivity while maintaining stability to the lithium metal negative electrode, thereby achieving good compatibility with the lithium metal negative electrode. On the other hand, the halide solid electrolyte membrane and the polymer solid electrolyte membrane provided in the embodiment of the present invention have excellent interface stability and higher density than the single-layer electrolyte membrane, so that the solid electrolyte membrane provided by the present invention has high mechanical properties, density and toughness on the basis of ensuring ion transmission, and is compatible with high-voltage positive electrode materials and lithium metal, effectively improving the interface impedance of each part in the system, improving the interface compatibility, and effectively improving the rate performance and cycle performance of the battery.

[0050] In some embodiments of the present invention, the halide solid electrolyte includes Li a M1X6、Li b M2X4 and Li 3-c M3 1- c M4 c Any one or more of X6;

[0051] Among them, 2≤a≤3, 0 <b≤2,0<c<1;

[0052] M1, M3 and M4 are each independently selected from any one of Sc, Y, La-Lu, In, Er, Yb, Zr or Hf; M2 is selected from any one or more of Co, Zn, Al, Cr, Mg or Ni, wherein La-Lu refers to lanthanide elements;

[0053] X is selected from any one or more of F, Cl, Br or I.

[0054] The halide solid electrolyte provided in the embodiment of the present invention has an oxidation potential higher than that of the oxide solid electrolyte, has the same deformability as the sulfide electrolyte and has a high -3 S / cm ionic conductivity, and has the prospect of large-scale application comparable to that of polymer electrolytes, namely, it has the advantages of high ionic conductivity, high voltage stability, excellent deformation performance, cost-effectiveness and large-scale preparation.

[0055] In some embodiments of the present invention, M3 is selected from metal elements with a valence of +3, and M4 is selected from metal elements with a valence of +4.

[0056] In some embodiments of the present invention, M3 is In, M4 is selected from Zr or Sc, and X is selected from F or Cl;

[0057] Or, M3 is Y or Er, M4 is Zr, and X is Cl;

[0058] Or, M3 is Yb, M4 is selected from Zr or Hf, and X is Cl.

[0059] When the halide solid electrolyte provided in the embodiment of the present invention is the above-mentioned doped solid electrolyte, the ionic conductivity and electrochemical window of the electrolyte can be more effectively improved, thereby more effectively improving the electrochemical performance of the halide-based all-solid-state battery.

[0060] In some embodiments of the present invention, the halide solid electrolyte is selected from any one or more of Li2M1X6, such as Li2ZrCl6, which can overcome the disadvantages of high cost and poor humidity stability of halide solid electrolytes, while having good deformability, air stability and high voltage positive electrode compatibility.

[0061] In some embodiments of the present invention, the halide solid electrolyte is selected from Li b Any one or more of M2X4.

[0062] When the halide solid electrolyte provided in the embodiment of the present invention is Li b When M2X4 is used, while ensuring the electrochemical performance of halide-based all-solid-state batteries, M2 is cheaper and more abundant than some expensive and scarce trivalent metal elements such as In, Sc and Y.

[0063] In some embodiments of the present invention, the binder includes PTFE. The present invention uses PTFE as a binder to dry-process the halide solid electrolyte membrane, and the PTFE is fibrous under shear force to form a three-dimensional matrix that can support and / or bind the electrolyte material, and the PTFE has excellent high-pressure stability.

[0064] In some embodiments of the present invention, the polymer solid electrolyte includes any one or more of PEO, PMMA, PAN, PS and PVDF.

[0065] In some embodiments of the present invention, the lithium salt includes any one or more of LiTFSI, LiDFOB, LiPF6, LiBF4, LiBOB, LiFSI and LiPO2F2. The embodiments of the present invention can effectively improve the ionic conductivity of the solid electrolyte membrane by introducing lithium salt.

[0066] In some embodiments of the present invention, the inorganic filler includes any one or more of LLZTO, LATP, LLZO, LLTP, LiPON and LZG. The embodiments of the present invention can weaken the interaction between the polymer and lithium ions, promote the dissociation of lithium salts and destroy the regularity of polymer chains, increase the free volume of the polymer, and improve the mobility of the chain segments by introducing inorganic fillers. In addition, the introduction of inorganic fillers can improve the ion migration number, mechanical properties, thermal stability and chemical / electrochemical stability of polymer-based electrolytes without sacrificing the flexibility and processability of the polymer.

[0067] In some embodiments of the present invention, based on the total mass of the halide solid electrolyte membrane as 100%, the content of the halide solid electrolyte is 95-98%, such as 95%, 96%, 97%, 98%, etc., and the content of the binder is 2-5%, such as 2%, 3%, 4%, 5%, etc. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0068] In some embodiments of the present invention, based on the total mass of the polymer solid electrolyte membrane as 100%, the content of the polymer solid electrolyte is 45-48%, such as 45%, 46%, 47%, 48%, etc., the content of the inorganic filler is 12-15%, such as 12%, 13%, 14%, 15%, etc., and the content of the lithium salt is 40%. However, the present invention is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0069] In some embodiments of the present invention, the thickness of the halide solid electrolyte membrane is 80-100 μm, for example, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc.

[0070] In some embodiments of the present invention, the thickness of the polymer solid electrolyte membrane is 80-120 μm, for example, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, etc.

[0071] The solid electrolyte membrane provided in the embodiment of the present invention has a relatively thin thickness and can effectively improve the energy density of the solid-state battery.

[0072] Accordingly, an embodiment of the present invention provides a method for preparing a solid electrolyte membrane, comprising:

[0073] (1) mixing a halide solid electrolyte and a binder and rolling them to obtain a halide solid electrolyte membrane;

[0074] (2) mixing a polymer solid electrolyte, a lithium salt, an inorganic filler and a solvent to obtain a polymer solid electrolyte slurry, and coating the polymer solid electrolyte slurry on the surface of the halide solid electrolyte membrane to obtain a solid electrolyte membrane;

[0075] Alternatively, the polymer solid electrolyte slurry is cast to obtain a polymer solid electrolyte membrane, which is then composited with a halide solid electrolyte membrane to obtain a solid electrolyte membrane.

[0076] Since the solvent is chemically incompatible with the halide solid electrolyte, compared with the traditional wet process, the embodiment of the present invention adopts a dry process to prepare the halide solid electrolyte membrane, thereby avoiding the influence of the solvent on the ionic conductivity of the electrolyte. It has the advantages of low cost, complete electrolyte structure without being damaged by solvents, and low amount of binder. It further improves the ionic conductivity while achieving the purpose of thicker electrodes and thinner electrolyte membranes.

[0077] In some embodiments of the present invention, the coating method in step (2) includes spraying, brushing, scraping, double-layer coating, etc.

[0078] In some embodiments of the present invention, the solvent in step (2) comprises NMP.

[0079] Accordingly, an embodiment of the present invention provides an all-solid-state battery, comprising the solid-state electrolyte membrane.

[0080] In some embodiments of the present invention, the all-solid-state battery includes a positive electrode sheet and a lithium metal negative electrode sheet. The halide solid electrolyte membrane in the solid electrolyte membrane provided in the embodiment of the present invention is close to the positive electrode sheet, and the polymer solid electrolyte membrane is close to the lithium metal negative electrode sheet, which can effectively improve the compatibility with the positive and negative electrode sheets.

[0081] Accordingly, an embodiment of the present invention provides a method for preparing an all-solid-state battery, comprising:

[0082] (1) rolling and laminating the halide solid electrolyte membrane and the positive electrode plate to obtain an integrated positive electrode, and coating the polymer solid electrolyte slurry on the surface of the negative electrode plate to obtain an integrated negative electrode;

[0083] (2) Roll-compressing the integrated positive electrode and the integrated negative electrode to obtain an all-solid-state battery.

[0084] The embodiments of the present invention utilize a solid electrolyte membrane and positive and negative electrode plates to prepare an all-solid-state battery through an integrated process, which can effectively improve the interface impedance of each part in the system, improve the interface compatibility, and thus effectively improve the rate performance and cycle performance of the battery.

[0085] Or, the preparation method comprises:

[0086] (1) coating a polymer solid electrolyte slurry on a surface of a halide solid electrolyte membrane to obtain a solid electrolyte membrane;

[0087] Or, a polymer solid electrolyte slurry is cast to obtain a polymer solid electrolyte membrane, and then the polymer solid electrolyte membrane is composited with a halide solid electrolyte membrane to obtain a solid electrolyte membrane;

[0088] (2) The positive electrode plate, the solid electrolyte membrane and the negative electrode plate are compounded to obtain an all-solid-state battery.

[0089] The preparation method of the halide solid electrolyte membrane comprises: mixing the halide solid electrolyte and the binder and then rolling to obtain the halide solid electrolyte membrane.

[0090] The preparation method of polymer solid electrolyte slurry comprises: mixing polymer solid electrolyte, lithium salt, inorganic filler and solvent to obtain polymer solid electrolyte slurry.

[0091] In some embodiments of the present invention, the method for preparing the polymer electrolyte slurry includes: dissolving an inorganic filler and a lithium salt in a solvent and mixing them evenly, and then adding a polymer solid electrolyte to obtain the polymer electrolyte slurry.

[0092] In some embodiments of the present invention, the mixing method is to perform magnetic stirring at a speed of 1000 r / min for 20 min, and then use ultrasonic mixing for 30 s.

[0093] Accordingly, an embodiment of the present invention provides a vehicle comprising the all-solid-state battery.

[0094] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its applications. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0095] If no specific techniques or conditions are specified in the examples, the conventional techniques or conditions in the art, or the techniques or conditions described in the literature, or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0096] Preparation Example 1

[0097] This preparation example provides a solid electrolyte membrane and a preparation method thereof, the preparation method comprising the following steps:

[0098] (1) LiZnCl4 and PTFE were added into a mortar in a mass ratio of 96:4 and uniformly mixed, and rolled to obtain a halide solid electrolyte membrane with a thickness of 90 μm;

[0099] (2) PEO, LiTFSI, and LLZTO were weighed in a mass ratio of 46:40:14. LLZTO and LiTFSI were first dissolved in NMP, and magnetically stirred at a speed of 1000 r / min for 20 min. Then, ultrasonic mixing was performed for 30 s. PEO was added and mixed to obtain a polymer solid electrolyte slurry. The slurry was then cast in a polytetrafluoroethylene culture dish and dried at 60° C. for 45 min. After removing the solvent, a polymer electrolyte membrane with a thickness of 100 μm was obtained.

[0100] (3) The halide solid electrolyte membrane and the polymer solid electrolyte membrane are laminated by double-layer roll pressing to obtain a solid electrolyte membrane.

[0101] Preparation Example 2

[0102] This preparation example provides a solid electrolyte membrane and a preparation method thereof, the preparation method comprising the following steps:

[0103] (1) Li 2.5 In 0.5 Zr 0.5 Cl6 and PTFE were added into a mortar at a mass ratio of 98:2 and uniformly mixed, and rolled to obtain a halide solid electrolyte membrane with a thickness of 80 μm;

[0104] (2) PVDF, LiDFOB, and LATP were weighed in a mass ratio of 48:40:12. LATP and LiDFOB were first dissolved in NMP and magnetically stirred at a speed of 1000 r / min for 20 min. Then, ultrasonic mixing was performed for 30 s. PVDF was added and mixed to obtain a polymer solid electrolyte slurry. The slurry was then evenly sprayed on the surface of the halide solid electrolyte membrane and then placed in a vacuum oven at 100° C. for 8 h to dry the solvent. The thickness of the polymer solid electrolyte membrane was 120 μm, and a solid electrolyte membrane was obtained.

[0105] Preparation Example 3

[0106] This preparation example provides a solid electrolyte membrane and a preparation method thereof, the preparation method comprising the following steps:

[0107] (1) Li2Zr4Cl6 and PTFE were added into a mortar in a mass ratio of 95:5, mixed evenly, and rolled to obtain a halide solid electrolyte membrane with a thickness of 100 μm;

[0108] (2) PAN, LiPF6, and LLZO were weighed in a mass ratio of 45:40:15. LLZO and LiPF6 were first dissolved in NMP and magnetically stirred at a speed of 1000 r / min for 20 min. Then, ultrasonic mixing was performed for 30 s. PAN was added and mixed to obtain a polymer solid electrolyte slurry. The slurry was then evenly brushed on the surface of the halide solid electrolyte membrane and then placed in a vacuum oven at 100°C for 8 h to dry the solvent. The thickness of the polymer solid electrolyte membrane was 80 μm, and a solid electrolyte membrane was obtained.

[0109] Preparation Example 4

[0110] This preparation example provides a solid electrolyte membrane and a preparation method thereof. The preparation method is the same as that of Preparation Example 2. The difference from Preparation Example 2 is that in this preparation example, the spraying in step (2) is replaced by brushing.

[0111] Preparation Example 5

[0112] This preparation example provides a solid electrolyte membrane and a preparation method thereof. The preparation method is the same as that of Preparation Example 2. The difference from Preparation Example 2 is that in this preparation example, the spraying in step (2) is replaced by scraping.

[0113] Examples 1-5

[0114] In this embodiment, the solid electrolyte membrane prepared in Preparation Examples 1-5 is respectively matched with a ternary positive electrode and a graphite negative electrode to assemble a mold battery. The specific preparation method is as follows:

[0115] (1) The ternary positive electrode sheet is prepared by coating: the ternary main material lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 O2, electrolyte Li3InCl6, conductive agent VGCF, and binder SBR were weighed in a mass ratio of 64.4:27.6:5:3 and added to the solvent. The solid content was 45%. After mixing evenly, they were placed on a flat carbon-coated aluminum foil. The height of the scraper was adjusted for coating. The compaction density was 3.2 g / cm 2 The electrode was then placed in a vacuum oven at 80°C for 10 hours for drying, and then the dried electrode was cut into 12 mm discs for later use. The entire process was carried out in an inert atmosphere.

[0116] (2) The graphite negative electrode sheet was prepared by coating method: graphite, conductive agent SP, and binder SBR were weighed in a mass ratio of 95:2:3 and added to the solvent NMP with a solid content of 45%. After mixing evenly, the mixture was placed on a flat carbon-coated aluminum foil and the height of the scraper was adjusted for coating. The compaction density was 1.6 g / cm 2The electrode was then placed in a vacuum oven at 80°C for 10 hours for drying, and then the dried electrode was cut into 12 mm discs for later use. The entire process was carried out in an inert atmosphere.

[0117] (3) Mold battery assembly: Use a powder tablet press to first press the graphite negative electrode sheet onto the short pole of the solid mold as the counter electrode, with a pressing pressure of 4T and holding the pressure for 1 minute. Then, place the solid electrolyte membranes prepared in Preparation Examples 1-5, press the tablets at 2T and hold the pressure for 1 minute, and place the ternary positive electrode sheet on the other side of the electrolyte membrane, with a pressing pressure of 4T and holding the pressure for 1 minute. Finally, tighten the sealing kit and screws to obtain the mold battery. The entire process is carried out in an inert atmosphere.

[0118] Example 6

[0119] This embodiment provides a battery cell and a method for preparing the same. The flow chart of the preparation method is as follows: Figure 1 As shown, the specific steps include:

[0120] (1) LiZnCl4 and PTFE were added to a mortar in a mass ratio of 96:4 and mixed evenly, and rolled to obtain a halide solid electrolyte membrane with a thickness of 90 μm; the halide solid electrolyte membrane and the positive electrode sheet were rolled and laminated to obtain an integrated positive electrode, and the positive electrode sheet was the same as the positive electrode sheet described in Example 1;

[0121] (2) PEO, LiTFSI, and LLZTO were weighed in a mass ratio of 46:40:14. LLZTO and LiTFSI were first dissolved in NMP, and magnetic stirring was performed at a speed of 1000 r / min for 20 min. Then, ultrasonic mixing was performed for 30 s, PEO was added, and the polymer solid electrolyte slurry was obtained by mixing. The slurry was then evenly sprayed on the negative electrode plate to prepare an integrated negative electrode. The thickness of the polymer solid electrolyte membrane was 100 μm. The negative electrode plate was the same as the negative electrode plate described in Example 1.

[0122] (3) Place the integrated positive electrode and the integrated negative electrode in a powder tablet press, press at a pressure of 5T and maintain the pressure for 1 minute. Finally, tighten the sealing kit and screws to obtain a mold battery. The entire process is carried out in an inert atmosphere.

[0123] Embodiment 7-8

[0124] This embodiment provides a battery cell and a method for preparing the same. The preparation method is the same as that of Embodiment 6. The difference from Embodiment 6 is that in this embodiment, the spraying in step (2) is replaced by brushing (Embodiment 7) and scraping (Embodiment 8).

[0125] Example 9

[0126] This embodiment provides a battery cell and a method for preparing the same, the method comprising the following steps:

[0127] (1) Li 2.5 In 0.5 Zr 0.5 Cl6 and PTFE are added to a mortar in a mass ratio of 98:2 and mixed evenly, and rolled to obtain a halide solid electrolyte membrane with a thickness of 80 μm; the halide solid electrolyte membrane and the positive electrode plate are rolled and laminated to obtain an integrated positive electrode, and the positive electrode plate is the same as the positive electrode plate described in Example 1;

[0128] (2) PVDF, LiDFOB, and LATP were weighed in a mass ratio of 48:40:12. LATP and LiDFOB were first dissolved in NMP, and magnetically stirred at a speed of 1000 r / min for 20 min. Then, ultrasonic mixing was performed for 30 s. PVDF was added and mixed to obtain a polymer solid electrolyte slurry. The slurry was then evenly sprayed on the negative electrode plate to prepare an integrated negative electrode. The thickness of the polymer solid electrolyte membrane was 100 μm. The negative electrode plate was the same as the negative electrode plate described in Example 1.

[0129] (3) Place the integrated positive electrode and the integrated negative electrode in a powder tablet press, press at a pressure of 5T and maintain the pressure for 1 minute. Finally, tighten the sealing kit and screws to obtain a mold battery. The entire process is carried out in an inert atmosphere.

[0130] Comparative Example 1

[0131] This comparative example provides a battery cell and a preparation method thereof. The preparation method is the same as that of Example 6, except that in this comparative example, the polymer solid electrolyte membrane in step (2) is replaced by a sulfide solid electrolyte membrane.

[0132] Specifically, the preparation method of the sulfide solid electrolyte membrane includes: weighing the sulfide electrolyte Li6PS5Cl and the binder SBR according to a mass ratio of 97:3, and weighing the solvent anisole according to a solid content of 40%. First, add SBR to the solvent anisole for stirring and dissolving, and magnetically stir at a speed of 1000r / min for 1h. Then add the corresponding mass of sulfide electrolyte Li6PS5Cl to the above solution for stirring and dispersion, magnetically stir at a speed of 1000r / min for 5h, and finally mix to obtain a sulfide solid electrolyte slurry. The above slurry is evenly and uniformly inverted on the coater for scraping, and the scraper thickness is 400μm / 300μm. The scraped membrane is placed on the coater, heated at 50°C until the membrane solvent evaporates, and then the membrane is flatly transferred to a vacuum oven, and heated at 100°C for 10h to obtain a sulfide solid electrolyte membrane.

[0133] It should be noted that the above-mentioned test cell is only an example listed to determine the performance of the solid electrolyte membrane, and the present invention is not limited to this kind of cell. The raw materials, proportions, parameters and processes of the positive electrode plates and the negative electrode plates can be replaced with other conventional raw materials, proportions, parameters and processes in the art, thereby forming a battery different from the test cell.

[0134] Performance Testing

[0135] The battery cells prepared in the examples and comparative examples were subjected to charge and discharge tests: the mold half-cell was charged to 4.2V at 0.1C constant current, charged to 0.05C cutoff at constant voltage, and discharged to 2.8V at 0.1C constant current.

[0136] The test results of the battery's charging capacity, discharging capacity and impedance are shown in Table 1:

[0137] Table 1

[0138]

[0139]

[0140] From the comparison between Example 6 and Comparative Example 1, it can be found that the solid electrolyte membrane provided by the present application has a more stable overall interface than the composite membrane of the halide membrane and the sulfide membrane, and the interface impedance is smaller after the battery is cycled for 50 cycles. At the same time, the battery also exhibits better cycle stability and first-cycle coulomb efficiency;

[0141] From the comparison between Examples 1-5 and 6-9, it can be found that the battery prepared by the integrated process has better performance. The mold battery assembled in Example 6-9 has excellent first-cycle gram capacity, good interface impedance after 50 cycles, and high capacity retention rate. It shows that the integrated process used in Example 6-9 has a more significant improvement in the interface contact between the electrolyte membrane and the positive and negative electrodes compared with Example 1, and the integrated process has a good promoting effect on the overall battery gram capacity and battery cycle life.

[0142] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0143] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane comprises a halide solid electrolyte membrane and a polymer solid electrolyte membrane composited on one side thereof, the halide solid electrolyte membrane comprises a halide solid electrolyte and a binder, and the polymer solid electrolyte membrane comprises a polymer solid electrolyte, a lithium salt and an inorganic filler.

2. The solid electrolyte membrane according to claim 1, characterized in that The halide solid electrolyte includes Li a M1X6、Li b M2X4 and Li 3-c M3 1-c M4 c Any one or more of X6; Among them, 2≤a≤3, 0 <b≤2,0<c<1; M1, M3 and M4 are each independently selected from any one of Sc, Y, La-Lu, In, Er, Yb, Zr or Hf; M2 is selected from any one or more of Co, Zn, Al, Cr, Mg or Ni; X is selected from any one or more of F, Cl, Br or I.

3. The solid electrolyte membrane according to claim 2, characterized in that: M3 is In, M4 is selected from Zr or Sc, and X is selected from F or Cl; Or, M3 is Y or Er, M4 is Zr, and X is Cl; Or, M3 is Yb, M4 is selected from Zr or Hf, and X is Cl.

4. The solid electrolyte membrane according to claim 1, characterized in that The binder comprises PTFE; And / or, the polymer solid electrolyte includes any one or more of PEO, PMMA, PAN, PS and PVDF.

5. The solid electrolyte membrane according to claim 1, characterized in that The lithium salt includes any one or more of LiTFSI, LiDFOB, LiPF6, LiBF4, LiBOB, LiFSI and LiPO2F2; And / or, the inorganic filler includes any one or more of LLZTO, LATP, LLZO, LLTP, LiPON and LZG.

6. The solid electrolyte membrane according to claim 1, characterized in that Based on the total mass of the halide solid electrolyte membrane being 100%, the content of the halide solid electrolyte is 95-98%, and the content of the binder is 2-5%; And / or, based on the total mass of the polymer solid electrolyte membrane being 100%, the content of the polymer solid electrolyte is 45-48%, the content of the inorganic filler is 12-15%, and the content of the lithium salt is 40%.

7. The solid electrolyte membrane according to claim 1, characterized in that The thickness of the halide solid electrolyte membrane is 80-100 μm; And / or, the polymer solid electrolyte membrane has a thickness of 80-120 μm.

8. An all-solid-state battery, characterized in that: The all-solid-state battery comprises the solid electrolyte membrane according to any one of claims 1 to 7.

9. A method for preparing an all-solid-state battery as claimed in claim 8, characterized in that: The preparation method comprises: (1) rolling and laminating the halide solid electrolyte membrane and the positive electrode plate to obtain an integrated positive electrode, and coating the polymer solid electrolyte slurry on the surface of the negative electrode plate to obtain an integrated negative electrode; (2) rolling the integrated positive electrode and the integrated negative electrode to obtain the all-solid-state battery; Or, the preparation method comprises: (1) coating a polymer solid electrolyte slurry on the surface of the halide solid electrolyte membrane to obtain a solid electrolyte membrane; Or, a polymer solid electrolyte membrane is obtained by casting a polymer solid electrolyte slurry and then compounded with the halide solid electrolyte membrane to obtain a solid electrolyte membrane; (2) Compounding the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet to obtain the all-solid-state battery; The preparation method of the halide solid electrolyte membrane comprises: mixing the halide solid electrolyte and the binder and rolling them to obtain the halide solid electrolyte membrane; The preparation method of the polymer solid electrolyte slurry comprises: mixing a polymer solid electrolyte, a lithium salt, an inorganic filler and a solvent to obtain the polymer solid electrolyte slurry.

10. A vehicle, characterized in that: The vehicle includes the all-solid-state battery of claim 8.

Citation Information

Cited By

  • Pebax / PEO composite solid-state battery and preparation method thereof

    CN122177898A